2018
DOI: 10.1242/bio.032102
|View full text |Cite
|
Sign up to set email alerts
|

Feeder-free differentiation of cells exhibiting characteristics of corneal endothelium from human induced pluripotent stem cells

Abstract: The purpose of this study was to devise a strategy for the derivation of corneal endothelial cells (CEnCs) from adult fibroblast-derived induced pluripotent stem cells (iPSCs). IPSCs were generated from an adult human with normal ocular history via expression of OCT4, SOX2, KLF4 and c-MYC. Neural crest cells (NCCs) were differentiated from iPSCs via addition of CHIR99021 and SB4315542. NCCs were driven toward a CEnC fate via addition of B27, PDGF-BB and DKK-2 to CEnC media. Differentiation of NCCs and CEnCs wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
54
0
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 50 publications
(65 citation statements)
references
References 59 publications
(85 reference statements)
0
54
0
3
Order By: Relevance
“…Since their first report in 2006, the reprogramming techniques have rapidly evolved and iPSCs have become a powerful "de-differentiated" cell type that can be deployed to generate specific cell lineages [85]. In corneal endothelial studies, iPSCs were reported to differentiate into CEC-like cells using a modified McCabe's protocol as described above [86]. Likewise, the chemically defined conditions using small molecules for "dual Smad inhibition" together with the modulations of BMP and Wnt pathways also generated cells displaying CEC-like features from iPSCs via NCC induction [87].…”
Section: Other Experimental Sources Of Corneal Endothelial Progenitorsmentioning
confidence: 99%
“…Since their first report in 2006, the reprogramming techniques have rapidly evolved and iPSCs have become a powerful "de-differentiated" cell type that can be deployed to generate specific cell lineages [85]. In corneal endothelial studies, iPSCs were reported to differentiate into CEC-like cells using a modified McCabe's protocol as described above [86]. Likewise, the chemically defined conditions using small molecules for "dual Smad inhibition" together with the modulations of BMP and Wnt pathways also generated cells displaying CEC-like features from iPSCs via NCC induction [87].…”
Section: Other Experimental Sources Of Corneal Endothelial Progenitorsmentioning
confidence: 99%
“…DNA microarray analysis revealed a close similarity between their corneal endothelial cells and primary cultured human corneal endothelial cells. In addition, Wagoner et al were able to derive corneal endothelial-like cells from iPS cells by modified McCabe’s protocol [17].…”
Section: Introductionmentioning
confidence: 99%
“…As an alternative to primary culture of hCECs, scientists have explored the differentiation of pluripotent stem cells to hCECs. Nevertheless, such differentiation protocols are still at an early developmental stage and need further improvements to prove that the genotype, phenotype and functionality of the differentiated cells resembles that of native hCECs [14][15][16]. Overall, the challenges associated with the primary culture of hCECs remain a barrier to their therapeutic application.…”
Section: Introductionmentioning
confidence: 99%